The Intercultural Sensitivity of Italian Correctional Officers Between Life Satisfaction and Burnout - Coppola, Ilaria (The prison journal, 2024)
Correctional officers (COs) play a crucial role within prisons. The purpose of this study is to analyze the intercultural sensitivity and individual and organizational well-being perceptions of COs. The participants were 400 COs employed in different prisons in northwestern Italy. Analysis of the results shows that there is a significant relationship between intercultural sensitivity and perceived emotional exhaustion and that this affects life satisfaction and thus the entire organization. More attention needs to be paid to the figure of the CO who interacts with people from different backgrounds often under difficult circumstances.